2009
DOI: 10.1111/j.1467-7652.2009.00431.x
|View full text |Cite
|
Sign up to set email alerts
|

The web‐building spider Theridion impressum (Araneae: Theridiidae) is not adversely affected by Bt maize resistant to corn rootworms

Abstract: Summary The growth of genetically engineered maize that produces the insecticidal protein Cry3Bb1 from Bacillus thuringiensis (Bt) is an effective method to control corn rootworms (Diabrotica spp.), which are threatening maize production in North America and Europe. In this study, the risk of Cry3Bb1‐expressing maize for the predatory spider Theridion impressum, a common species in European maize fields, was assessed. Quantification of Cry3Bb1 in potential prey species collected in Bt maize plots and prey spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
87
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 33 publications
7
87
0
Order By: Relevance
“…This is consistent with other studies, which have shown that theridiid spiders screen positive for Cry3Bb1 (Meissle & Romeis, 2009) and araneid spiders screen positive for Cry1Ab (Ludy & Lang, 2006), both from transgenic Bt corn fields in Europe. However, pollen may not be a major route to Bt-endotoxin exposure for all types of Bt crops and all spiders.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This is consistent with other studies, which have shown that theridiid spiders screen positive for Cry3Bb1 (Meissle & Romeis, 2009) and araneid spiders screen positive for Cry1Ab (Ludy & Lang, 2006), both from transgenic Bt corn fields in Europe. However, pollen may not be a major route to Bt-endotoxin exposure for all types of Bt crops and all spiders.…”
Section: Discussionsupporting
confidence: 82%
“…The presence of Cry3Bb1 in corn-fed crickets was much higher (100% for both Rootworm and Plus) with similarly high presence in cricket-fed wolf spiders (80% and 60% for Rootworm and Plus); this result was surprising given that a higher percentage of field-collected spiders from Corn Borer and Plus fields were positive for Cry1Ab compared to Rootworm and Plus fields for Cry3bb1. Tri-trophic movement studies involving spiders (reviewed in Peterson et al, 2011) also report movement of various Bt proteins into lycosid, linyphiid, and theridiid spiders from lepidopteran or hemipteran prey fed Bt rice and lacewing, spider mite or corn rootworm prey fed Bt corn (Chen et al, 2009;Han et al, 2015;Jiang et al, 2004;Meissle & Romeis, 2009;Tian et al, 2010). In addition, Meissle & Romeis (2012) found that although Cry3Bb1 was transferred to a theridiid spider via prey consumption, the Bt proteins were rapidly excreted, with Cry3Bb1 concentration decreasing by approximately 90% within five days of feeding.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel we also tested spider mites that had fed on another Bt maize line expressing the Coleoptera-active Cry3Bb1 toxin [6]. There we were able to compare the ELISA values to those from ladybird beetle larvae that were collected in field with the same Bt maize [18]. This comparison revealed that the Cry protein concentration detected in larvae from our laboratory bioassay was between 160-and 330-fold higher than that measured in field-collected larvae [6].…”
Section: Discussionmentioning
confidence: 77%
“…Spider mites served as an ideal toxin carrier because they are prey of ladybird larvae and are known to contain very high amounts of Cry protein when compared to other herbivores [6,[16][17][18]. Furthermore, we had shown in a previous sensitive insect bioassay that the Cry1Ab ingested by spider mites is biologically active [19], and the spider mites themselves are not affected when feeding on Cry1Ab-expressing Bt maize [16].…”
Section: Discussionmentioning
confidence: 99%
“…The Cry proteins in Bt cotton are produced throughout the entire growing season, and so target and nontarget arthropods have ample opportunity for exposure to these proteins. These include predators and parasitoids that may be exposed when they feed on arthropods that have consumed plant tissue containing Bt proteins (Harwood et al 2005;Obrist et al 2005Obrist et al , 2006Torres et al 2006Torres et al , 2008Meissle and Romeis 2009). Such tritrophic interactions may have consequences for insect pest management and should be examined as part of an environmental risk assessment.…”
mentioning
confidence: 99%